The Effect of Administrative Information Systems on projects Administration: An Exploratory Study of an Administrative Leaders Sample in Asia cell Communications Company in Iraq (Eurasian Journal of History, Geography and Economics, 2023)
The study attempts to find out the effect of the administrative information system on projects administration for a sample of employees in Asiacell Company. In order to achieve the objective of the study, the descriptive analytical approach was used. To achieve this, the research questionnaire was designed, as it was distributed to (80) questionnaires on a simple random sample of employees. The study found that there is a significant correlation between the components of administrative information systems and projects administration in the researched company. As for the most important recommendations, the company should pay attention to information systems units and specialized individuals to develop information systems, and then achieve the main objective of providing information to decision makers and beneficiaries, especially the senior administration of the company